Amchitka and the bomb : nuclear testing in Alaska - Kohlhoff, Dean (Book collections on Project MUSE., 2002)
From 1965 through 1971, the US set off three underground atomic blasts in the remote wilderness of the Aleutian islands off the coast of Alaska. Detailing how these nuclear explosions were planned and conducted in spite of protests by political and civilian groups, this book traces the environmental impact of the blasts on the Aleutian wildlife refuge system and examines the social and political fallout from the tests on Aleut civilian populations.